2021
DOI: 10.3390/su13147523
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of ICT Support and the EFQM Criteria on Sustainable Business Excellence in Higher Education Institutions

Abstract: The problem of sustainable business excellence has been investigated according to different aspects in different fields. For a more detailed analysis, it is necessary to develop an integrative sustainable business excellence model, respecting the baseline model of business excellence according to the European Foundation of Quality Management, with the possibility of defining the relationships and levels of significance of different variables. The primary goal of this paper is to present a developed integrative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 94 publications
(108 reference statements)
1
3
0
1
Order By: Relevance
“…Specifically, 12 of the 15 hypotheses were confirmed at high levels of significance (H1, H2, H4, H5, H7, H8, H9, H10, H11, H12, H13, H15). Moreover, the results showed that leadership had positive effects on strategy (0.760) and people (0.468), which are supported by previous literature (Belvedere et al 2018;Ðor dević et al 2021;Kaplani 2023;Para-González et al 2021;Zhang et al 2021). These findings underscore the critical role that leadership plays in formulating policies and motivating people; therefore, public sector services need to pay great attention to the leadership cultivated in their organizations and provide guidance on how it can be effective.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, 12 of the 15 hypotheses were confirmed at high levels of significance (H1, H2, H4, H5, H7, H8, H9, H10, H11, H12, H13, H15). Moreover, the results showed that leadership had positive effects on strategy (0.760) and people (0.468), which are supported by previous literature (Belvedere et al 2018;Ðor dević et al 2021;Kaplani 2023;Para-González et al 2021;Zhang et al 2021). These findings underscore the critical role that leadership plays in formulating policies and motivating people; therefore, public sector services need to pay great attention to the leadership cultivated in their organizations and provide guidance on how it can be effective.…”
Section: Discussionsupporting
confidence: 86%
“…A typical example is the application of the EFQM Excellence Model in higher education in Serbia and Russia, with the aim of achieving sustainable excellence. This example shows that the education sector, for which the model was not originally designed, could not adapt to the requirements of the excellence model, due to lack of experience and the pressure to meet expectations immediately [178]. If adapted to the culture of each place, the EFQM model could contribute to enhancing excellence at all levels of education and achieving high levels of performance and improvement.…”
Section: Discussionmentioning
confidence: 99%
“…It was perceived that the use of the EFQM excellence model's self-assessment in the public sector has lagged behind that in the private sector. This was somewhat because of the lag in adapting the EFQM excellence model for public sector use, and due to the lack of pressure to respond to customers through continuous improvement in the public sector when compared with the private sector (Đorđević et al ., 2021). However, in terms of constraints, especially financial resources, the solution should be in “soft” factors.…”
Section: Theoretical Implicationsmentioning
confidence: 99%